2013
DOI: 10.3851/imp2683
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Role of Adjunctive Corticosteroids in Herpes Simplex Virus Encephalitis: Is Timing Critical for Safety and Efficacy?

Abstract: Experimental and clinical observations suggest a benefit from adjunctive steroid therapy in HSVE. Nevertheless, current evidence is not yet sufficient to endorse this approach as a standard of practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 58 publications
(116 reference statements)
0
24
2
1
Order By: Relevance
“…A retrospective analysis of a larger number of patients with HSE showed that administration of adjunctive glucocorticoids was an independent predictor of a better neurological outcome . Also, a recent review of animal and clinical studies suggests a benefit of adjunctive corticosteroids therapy in HSE . However, clear evidences are still lacking to translate this approach into clinical practice.…”
Section: Immunomodulatory Strategies Against Herpes Simplex Virus Encmentioning
confidence: 99%
“…A retrospective analysis of a larger number of patients with HSE showed that administration of adjunctive glucocorticoids was an independent predictor of a better neurological outcome . Also, a recent review of animal and clinical studies suggests a benefit of adjunctive corticosteroids therapy in HSE . However, clear evidences are still lacking to translate this approach into clinical practice.…”
Section: Immunomodulatory Strategies Against Herpes Simplex Virus Encmentioning
confidence: 99%
“…[24] Corticosteroids Corticosteroids as an adjunct treatment for HSE are still controversial. One study showed that corticosteroids increase patient benefit [25] but they are not routinely recommended [3,16,26] as a large prospective randomised trial is still needed. However, steroid administration is recommended in situations where HSE patients show severe cerebral edema that could result in severe brain swelling, coning and death and lumbar puncture is to be avoided.…”
Section: Antiviral Therapymentioning
confidence: 99%
“…Steroids have also been suggested for treatment in HSVE given the strong inflammatory cascade and immune response seen with the infection. Case reports of concomitant or delayed administration of corticosteroids compared with acyclovir alone have showed favorable outcomes, 16 and a randomized trial evaluating their timing and utility is underway (German Trial of Acyclovir and Corticosteroids in Herpes-Simplex-Virus-Encephalitis [GACHE]). 17…”
Section: Treatmentmentioning
confidence: 99%